COMPLICATIONS OF DISEASES AND SERUM CREATININE LEVELS IN DIABETIC PATIENTS - Rizal Rizal; Syawal Alfikry Kaimudin; Wulan Panduwi Melasari (Universitas 17 Agustus 1945 Jakarta, 2025)
Diabetes mellitus, a metabolic disease, is a predisposing factor for diabetic nephropathy. This condition is defined by renal damage and hypercreatininemia in individuals with diabetes. Diabetic nephropathy is a multifactorial condition, with comorbidities playing a significant role in its pathogenesis. The purpose of this study was to determine the association between complicatin of diseases and serum creatinine levels among Diabetes Mellitus patients at the Nania Community Health Center, Ambon. The study adopted a cross-sectional design. A simple random sample was drawn for the study. The measurement of serum creatinine concentration is carried out using the Jaffé Reaction (Kinetic Method) at the Laboratory of the Maluku Province Special Regional Hospital. Chi-Square test was used to statistically analyze the data. A total of 30 patients were included in this study. Of these, 17 patients (56.7%) had complicatin, 10 patients (33.3%) had abnormal creatinine levels, and 7 patients (23.3%) had normal creatinine levels. Furthermore, 13 patients (43.3%) without complication had normal creatinine levels. The results of the Chi-Square test demonstrated a statistically significant association (p = 0.001) was found between complication and serum creatinine levels in Diabetes Mellitus patients. The results of statistical analysis demonstrated a statistically significant association (p = 0.001) between complication of diseases and serum creatinine concentration in patients with Diabetes Mellitus. This suggests that the presence of complication increases the likelihood of abnormal serum creatinine, consequently raising the possibility of diabetic nephropathy.